2020
DOI: 10.3389/fgene.2020.593688
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Characterization of a Novel NONO Intronic Mutation in a Fetus With X-Linked Syndromic Mental Retardation-34

Abstract: Background The NONO gene is located on chromosome Xq13.1 and encodes a nuclear protein involved in RNA synthesis, transcriptional regulation, and DNA repair. Hemizygous variants in NONO have been reported to cause mental retardation, X-linked, syndromic 34 (MRXS34) in males. Due to the scarcity of clinical reports, the clinical characteristics and mutation spectrum of NONO-related disorder have not been entirely determined. Methods We reported a fetus with hypoplastic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Less clear is the involvement of NONO in heart defects that has been confirmed to be present in the most of NONO -patients. From the first description of a subjects with a pathogenic variant of NONO presenting with LVNC [ 2 ], this cardiac defect was reported in the other 12 male patients, making this clinical feature as a distinctive sign of this disorder [ 2 , 3 , 4 , 5 , 6 , 7 ]. Based on literature review, LVNC was isolated in two cases (2/13; 15%), whereas was reported in association with other structural heart defects in the others (11/13; 85%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less clear is the involvement of NONO in heart defects that has been confirmed to be present in the most of NONO -patients. From the first description of a subjects with a pathogenic variant of NONO presenting with LVNC [ 2 ], this cardiac defect was reported in the other 12 male patients, making this clinical feature as a distinctive sign of this disorder [ 2 , 3 , 4 , 5 , 6 , 7 ]. Based on literature review, LVNC was isolated in two cases (2/13; 15%), whereas was reported in association with other structural heart defects in the others (11/13; 85%).…”
Section: Discussionmentioning
confidence: 99%
“…Effectively, since then, 73% of subjects affected by MRXS34 were reported showing cardiac anomalies, in particular LVNC, but also septal defects and right-sided lesions as Ebstein’s anomaly [ 3 , 4 , 5 , 6 ]. Heart defects were also disclosed as the peculiar clinical characteristic of a series of male fetuses with NONO variants detected by WES analysis [ 5 , 7 ]. Therefore, this characteristic associated with the neurodevelopmental phenotype could actually address the diagnosis of NONO -related disorder.…”
Section: Introductionmentioning
confidence: 99%
“…LQTS is a type of inherit cardiovascular disease that induces the prolonged duration of QT interval. Besides, some cases also demonstrated that LQTS presents as AVB (Aziz et al, 2010;Oka et al, 2010;Sun et al, 2022). It has been considered that AVB could be due to LQTS as a kind of pseudo AVB.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 10 live‐born and 7 prenatal cases with either maternally inherited or de novo null variants in NONO were reported in 14 families (Carlston et al, 2019; Mircsof et al, 2015; Reinstein et al, 2016; Scott et al, 2017; Sewani et al, 2020; Sun, Han, et al, 2020; Sun, Zhou, et al, 2020). Through international collaboration, we extended the published cohort by six live‐born males with NONO null variants, including the first in‐frame splice variant.…”
Section: Introductionmentioning
confidence: 99%